2011
DOI: 10.1590/s0102-67202011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Perfil dos pacientes ambulatoriais com doenças inflamatórias intestinais

Abstract: -Introduction -The inflammatory bowel diseases are chronic illnesses that significantly affect the quality and patients life expectancy. There is clinical polymorphism and the therapeutic approach has been modified in recent years. Aim -To re-analyze the profile of outpatient patients studying the behavior of the disease, its prevalence and therapeutic approach. Methods -Was conducted a cross-sectional study of the last 2010 update database of patients with inflammatory bowel disease. The items analyzed were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
16
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 17 publications
(18 reference statements)
5
16
0
8
Order By: Relevance
“…Although telehealth defined as health-care services provided to people separated by distance and time is available by using technologies such as telephones, computers, or interactive video streaming, these resources are underutilized in South America for improving patient assistance programs despite the widespread use of both landlines and cell phones by these populations (13) . Similar to the epidemiological studies on the profile of patients with IBD conducted by Kleinubing-Júnior et al and Barros et al, the extent of involvement of UC in this study showed a prevalence of extensive colitis (E3) and rectitis/proctitis (E1) (3,8) . The Montreal classification, owing to its diagnostic and therapeutic implications, has been increasingly used in patients with CD.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Although telehealth defined as health-care services provided to people separated by distance and time is available by using technologies such as telephones, computers, or interactive video streaming, these resources are underutilized in South America for improving patient assistance programs despite the widespread use of both landlines and cell phones by these populations (13) . Similar to the epidemiological studies on the profile of patients with IBD conducted by Kleinubing-Júnior et al and Barros et al, the extent of involvement of UC in this study showed a prevalence of extensive colitis (E3) and rectitis/proctitis (E1) (3,8) . The Montreal classification, owing to its diagnostic and therapeutic implications, has been increasingly used in patients with CD.…”
Section: Discussionsupporting
confidence: 89%
“…The data released in April 2016 by the department of pharmaceutical care and strategic inputs of the state of Rio de Janeiro are consistent with those obtained in the outpatient service. That publication indicated that 58.92% of patients with IBD were women and 41.08% were men (3,4,8,14) . In contrast, most European studies showed a higher prevalence of IBD among men; in European countries, women primarily develop CD and men develop UC (2,12) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Estomias intestinais podem ser realizadas por doenças benignas ou malignas, criadas em condições de cirurgia eletiva ou de emergência, construídas no intestino delgado ou colón, podendo ser consideradas temporária ou permanente, e ainda para fins curativos ou paliativos (4) . Esses estomas são causados por traumatismos, doenças congênitas, doenças inflamatórias (doença de Crohn, retocolite ulcerativa crônica, diverticulite), tumores e câncer do intestino (cólon) (5) .…”
unclassified